«Fent una reixa ofici de vicari». La paradoxa de la reixa en la poesia de Vicent Garcia i Francesc Fontanella. - MARCO, MARC SOGUES (Scripta, 2023)
The present article starts from the comparison between the cliché of love from afar (or absent love), referred to that kind of texts in which the poetic self is separated from the lady he loves, and what is proposed to be called 'grilled love', which happens in the poetry of monastic love when a nun and her suitor are separated only by the minimal but insurmountable distance of the grill of a locutory. The work analyzes the parallels and divergences between the two clichés and illustrates them with the analysis of a romance by Francesc Fontanella and three sonnets by Francesc Vicent Garcia, Rector of Vallfogona. Also, it is pointed out a case of intertextual relationship between the two authors that had not been detected until now.